God, Why This Evil? - Little, Bruce A. (Hamilton Books, 2012)
God: Why This Evil? examines the more traditional Christian explanation for why God permits evil in this world and offers an alternative explanation. After reviewing several greater-good explanations, that is God allows evil in order to bring about some greater good, Professor Little concludes that such explanations are neither theologically necessary nor practically helpful. In response, theological and philosophical issues related to this great question are clarified, concluding with an alternative explanation for the existence of evil in this world. The major point being that some evil may very well be gratuitous (i.e., has a reason, but no purpose), but does not count against the moral perfections of God, limit His power, or restrict His sovereignty. In conclusion, key Bible passages are examined with an application of the alternative position to the great question of why God allows so much evil in this world.